Antioxidant and anti-diabetic properties, and phytochemical profile of different parts of Mangifera odorata Griff. fruit - Lasano, Nur Fatimah (2019)
Mangifera odorata G. or known as “kuini” in Malay represent the hybrid form between M. indica (mango) and M. foetida (bacang). Mango and its fruit wastes are known for its high nutritive and pharmaceutical value, however there was a lack of scientific data focusing on the nutritional composition and biological activities of M. odorata fruit. In this study, peel, pulp and seed kernel of M. odorata fruit were investigated for their nutritional composition. Then, the samples were freeze-dried and extracted using several extraction solvents (acetone, ethanol, methanol at 60% v/v and water), and their effect on antioxidants (TPC, TFC, FRAP assay, and DPPH assay) and anti-diabetic activities (α-amylase and α-glucosidase inhibition assay) were determined. Next, the ethanolic extract of peel, pulp, and seed kernel from M. odorata was further analysed for their phytochemical profile using ultra-high-performance liquid chromatography electrospray ionization orbitrap tandem mass spectrometry (UHPLC-ESI-Ortbitrap-MS/MS). The results indicated that the seed kernel is rich in fat, protein, carbohydrate, and ash (2.76, 2.62, 43.31 and 1.29 g/100 g fresh fruit, respectively). Meanwhile, the peel contains significantly higher fibre, potassium, sulfur, aluminum, calcium, manganese, iron, boron, β-carotene and ascorbic acid compared to seed kernel and pulp. Results show that the seed kernel has the highest TPC and exhibits the strongest scavenging activity compared to other samples. Among the tested solvents, 60% ethanol extract showed highest reducing power in peel and pulp. In addition, acetone at 60% from peel and pulp extracts showed high scavenging activity and TPC in peel and seed kernel. Anti-diabetic assays revealed that the peel, pulp and seed kernel were not active inhibitors of α-amylase and α-glucosidase. The most abundant compounds identified in M. odorata fruit were phenolic acid, ellagic acid, and flavonoid, which mostly found in peel and seed kernel. In conclusion, M. odorata by-products (peel and seed kernel) contained a high nutritional value with good antioxidant properties, hence might be potentially used as a functional food ingredient.